2021
DOI: 10.3390/molecules26237249
|View full text |Cite
|
Sign up to set email alerts
|

Structural Analysis of Saccharomyces cerevisiae Dihydroorotase Reveals Molecular Insights into the Tetramerization Mechanism

Abstract: Dihydroorotase (DHOase), a dimetalloenzyme containing a carbamylated lysine within the active site, is a member of the cyclic amidohydrolase family, which also includes allantoinase (ALLase), dihydropyrimidinase (DHPase), hydantoinase, and imidase. Unlike most known cyclic amidohydrolases, which are tetrameric, DHOase exists as a monomer or dimer. Here, we report and analyze two crystal structures of the eukaryotic Saccharomyces cerevisiae DHOase (ScDHOase) complexed with malate. The structures of different DH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(26 citation statements)
references
References 67 publications
1
25
0
Order By: Relevance
“…The inhibitory effect of myricetin has been established in several helicases such as the SARS coronavirus helicase [ 55 , 56 ], the replicative DnaB helicase [ 57 , 58 , 59 ], the RSF1010 RepA helicase [ 60 ], and the PriA helicase [ 61 ]. Moreover, myricetin could also inhibit the activities of several cyclic amidohydrolases [ 62 ] such as the bacterial enzymes dihydropyrimidinase [ 63 , 64 ], dihydroorotase [ 65 , 66 , 67 , 68 , 69 ], and allantoinase [ 68 , 70 ]. Thus, myricetin may be a competent “dirty drug” (a multitarget drug) against ESKAPE pathogens [ 17 ] and has broad application prospects.…”
Section: Discussionmentioning
confidence: 99%
“…The inhibitory effect of myricetin has been established in several helicases such as the SARS coronavirus helicase [ 55 , 56 ], the replicative DnaB helicase [ 57 , 58 , 59 ], the RSF1010 RepA helicase [ 60 ], and the PriA helicase [ 61 ]. Moreover, myricetin could also inhibit the activities of several cyclic amidohydrolases [ 62 ] such as the bacterial enzymes dihydropyrimidinase [ 63 , 64 ], dihydroorotase [ 65 , 66 , 67 , 68 , 69 ], and allantoinase [ 68 , 70 ]. Thus, myricetin may be a competent “dirty drug” (a multitarget drug) against ESKAPE pathogens [ 17 ] and has broad application prospects.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we identified that S. purpurea-root-acetone could inhibit the enzymatic activity of huDHOase. DHOase is the third enzyme in the de novo biosynthesis pathway of pyrimidine nucleotides (Figure 7A) and is considered an attractive target for potential antimalarial, anticancer, and antipathogen chemotherapy [17,[39][40][41]43,[54][55][56][57][58][59][60][61]. This enzyme contains a binuclear metal center (Znα/Znβ) and a residue Asp1686 (Figure 7B) crucial for the catalysis [42,[62][63][64][65].…”
Section: Discussionmentioning
confidence: 99%
“…Dihydroorotase (DHOase) [17,[39][40][41] is the third enzyme in the de novo biosynthesis pathway for pyrimidine nucleotides [42] and an attractive target for potential anticancer chemotherapy [43,44]. When the urea cycle is dysregulated, nitrogen will be redirected and used by the multifunctional enzyme CAD (carbamoyl phosphate synthetase/aspartate transcarbamoylase/DHOase) to increase pyrimidine synthesis in cancer cells [45].…”
Section: Dihydroorotase Inhibitory Potentialmentioning
confidence: 99%
See 1 more Smart Citation
“…14 The active site residues His56, His58, His168, His227, and Asp302, that coordinate the two Zn ions (Figure 1A), are invariant among DHOase structures. 5,[11][12][13][14] KCX137 is invariant in bacterial type II, III, and human, 11 as well as active fungal 13 DHOases. The aspartate that coordinates the two Zn ions in bacterial type I, for example, BaDHOase, is invariant in this subtype.…”
Section: Structure Solution and Refinementmentioning
confidence: 99%